Pengaruh Brand Image Dan Country Of Origin Melalui Word Of Mouth Terhadap Keputusan Pembelian Online Produk Erigo (Studi Kasus Mahasiswa Universitas Islam Malang) - Aliwafa Aliwafa; Jeni Susyanti; Andi Normaladewi (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This time people live in modern times with the development of knowledge and technology, make it easier for people to find their needs such as clothes that follow fashion trends. There are many ways to finds out what fashion trends are currently rife in society, namely through social media. This is also influenced by the existence of brand image which is determines consumers to buy products online. Consumers judge where products come from (country of origin) and many consumers know brands through online reviews and word of mouth to make decisions to buy fashion products. This study aims to determine the effect of brand image, country of origin through word of mouth on purchasing decisions for Erigo's online products. In students of the Islamic University of Malang. This research uses quantitative methods. The sampling method uses the Ferdinand formula with a purposive sampling technique as a sample of 100 respondents. The tests carried out are validity test, reliability test, normality test, path analysis and hypothesis testing with the application of SPSS 25. The results of research on brand image (X1) and country of origin (X2) through word of mouth (Z) have a significant effect on purchasing decisions (Y) on the online product Erigo among students at the Islamic University of Malang Keywords: Brand Image, Country Of Origin, Word Of Mouth, Purchasing Decision